Effect of interruption in sedentary behavior on glycemic control in gestational diabetes - Trujillo Gittermann, Luz María (2023)
Physical activity produces beneficial effects in pregnant women. In spite of this, mostof them present high levels of sedentary behavior. The objective of the study wasto demonstrate the effect of a break in sedentary behavior on metabolic controlin a 36-year-old patient with gestational diabetes. The intervention consisted ofreorganizing her daily routine and performing a sedentary behavior break protocol.The patient achieved optimal metabolic control after the beginning of the interventionand until the end of pregnancy. The sedentary behavior break protocol added to thereorganization of the patient's routine proved to be effective in achieving glycemiccontrol and avoiding complications associated with gestational diabetes.